Antenna misalignment effects in 100 Gbit/s D‐band wireless transmissions. Issue 6 (30th March 2017) - Puerta, R.; Yu, Jianjun; Li, Xinying; Xu, Yuming; Vegas Olmos, J.J.; Tafur Monroy, I.
ABSTRACT: We report an operational photonics‐enabled 100 Gbit/s D‐band antenna polarization multiplexing system (2 × 2 MIMO) with a carrier frequency of 141 GHz, and experimentally explores antenna misalignment effects on the signal performance in terms of bit error rate. Misalignments from −10 to 10 degrees were evaluated for both the E ‐ and H ‐plane, highlighting the strict requirements needed to maintain a signal performance below forward‐error correction codes thresholds. Our findings indicate tolerable misalignments are below 1 degree, hinting beam steering as a must for future D‐band communication links. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1431–1434, 2017